Kepeminpinan Kristen dalam Masyarakat Majemuk untuk Menjaga Keharmonisan dan Keberagaman - Dedi Dedi; Ester Novita Desi; Asnawati Saogo; Semuel Linggi Topayung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This article discusses the role of leadership in pluralistic societies and how leadership can foster harmony in diversity. Leadership in this context goes beyond decision-making; it also involves the ability to unite various elements of society that come from different cultural, social, and religious backgrounds. The research reveals that effective leadership in a pluralistic society requires not only skills in managing conflicts and differences, but also qualities such as integrity, empathy, and the courage to make fair decisions. Furthermore, multicultural education and the implementation of inclusive leadership principles, based on universal values such as tolerance, mutual respect, and cooperation, play a crucial role in creating a harmonious society. Through this approach, societies can more easily overcome the challenges of diversity and build peaceful and prosperous communities.